The Effect of Asset Structure and Profitability on Capital Structure of Consumer Goods Companies Listed on IDX 2020–2024 - Henni Savitri; Meigia Nidya Sari (Harmoni Economics: International Journal of Economics and Accounting, 2025)
This study investigates the influence of asset structure and profitability, measured by return on assets (ROA), on the capital structure of consumer goods manufacturing companies listed on the Indonesia Stock Exchange (IDX). The capital structure, indicated by the debt-to-equity ratio (DER), plays a crucial role in determining the financial stability and growth potential of companies. The analysis incorporates both partial and simultaneous effects, highlighting the interrelationship between profitability, asset structure, and financial leverage. The study employs a descriptive quantitative approach, applying multiple linear regression to analyze data from 150 observations across 30 firms within the consumer goods sector. The period under review provides a comprehensive overview of corporate financial strategies, considering factors such as firm size, industry trends, and market conditions. The results demonstrate that both ROA and asset structure significantly influence the DER, both independently and interactively. Specifically, the findings show that higher profitability, reflected in a higher ROA, tends to lower the reliance on debt financing, thereby reducing the DER. Conversely, companies with more substantial and less liquid asset structures, such as property, plant, and equipment, tend to have higher debt levels, as these assets can serve as collateral for borrowing. The interaction between ROA and asset structure further underscores the complexity of capital structure decisions, where companies must balance profitability with asset composition to optimize their financial leverage. These findings provide valuable insights for financial managers and investors in consumer goods manufacturing companies, emphasizing the critical role of profitability and asset composition in shaping corporate capital structure decisions. Understanding the dynamics of these variables is essential for making informed decisions that support long-term business sustainability and competitiveness in the capital markets.